Exploring The Mediating Role of Digital Literacy in Enhancing Economic Teacher Candidates' Readiness: Insight from Teacher Competence, Critical Thinking Skills, and Teaching Experience - Sri Handayani; Rizza Megasari; Rizky Dwi Putri; Ana Dhaoud Daroin; Mohamad Zuber Abd. Majid; Wiwin Hartanto; Intan Nurwibawanti; Sindi Wahyu Purbowati (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: Teacher readiness remains a critical issue in improving the quality of economics teacher education programs. This study aims to analyse the relationship between teacher competence, critical thinking skills, and teaching experience on the readiness of economics teacher candidates. Additionally, the study examines the mediating role of digital literacy in strengthening these relationships. Method: This study employed a quantitative approach using covariance-based structural equation modelling (CB-SEM). Data were collected from 103 students of Economics Education Study Programs from both public and private universities in Java. The analysis was conducted using AMOS software version 30 to test the proposed hypotheses regarding the mediating effect of digital literacy on the relationships between teacher competence, critical thinking skills, teaching experience, and prospective teacher readiness.  Results: The findings reveal that digital literacy plays a significant mediating role in enhancing the readiness of economics teacher candidates. In particular, digital literacy strengthens the relationship between teaching experience and prospective teacher readiness. Furthermore, competence and critical thinking skills also contribute positively to teacher readiness when supported by adequate digital literacy capabilities. Novelty: This study highlights digital literacy as a strategic mediator that integrates pedagogical competence, critical thinking, and teaching experience in preparing economics teacher candidates for digitally driven learning environments. The findings provide a new perspective for teacher education programs by emphasizing digital literacy development as a core component in strengthening prospective teacher readiness in the era of digital transformation.